2010
DOI: 10.1097/qai.0b013e3181de8d26
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Quadrivalent Human Papillomavirus (Types 6, 11, 16, and 18) Vaccine in HIV-Infected Children 7 to 12 Years Old

Abstract: Background-Quadrivalent human papillomavirus vaccine (QHPV) is >95% effective in preventing infection with vaccine-type human papillomavirus. The safety and immunogenicity of QHPV are unknown in HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 38 publications
8
146
0
4
Order By: Relevance
“…As yet there are limited data on safety, immune response and efficacy of the HPV vaccine in HIV+ women, although studies are on-going. Although data on the safety of the quadrivalent vaccine in HIV-infected children has been demonstrated, efficacy of the currently available HPV vaccines in women or girls with HIV has not yet been established (Levin et al 2010).…”
Section: Primary Prevention Of Hpv/cervical Cancermentioning
confidence: 99%
“…As yet there are limited data on safety, immune response and efficacy of the HPV vaccine in HIV+ women, although studies are on-going. Although data on the safety of the quadrivalent vaccine in HIV-infected children has been demonstrated, efficacy of the currently available HPV vaccines in women or girls with HIV has not yet been established (Levin et al 2010).…”
Section: Primary Prevention Of Hpv/cervical Cancermentioning
confidence: 99%
“…В настоящее время накоплены результаты клини-ческих исследований у пациентов разных возрастов и полов, страдающих ВИЧ-инфекцией, которые проде-монстрировали высокий уровень безопасности и имму-ногенности квадривалентной вакцины [61][62][63][64].…”
Section: вакцинация групп рискаunclassified
“…-Human papillomavirus (HPV) vaccine. Data of quadrivalent human papillomavirus vaccine (QHPV) in HIV-infected children (60% female) aged from 7 to 12 years, with a CD4% ≥15 and on stable antiretroviral therapy showed that the vaccine is safe and immunogenic for the 4 antigens (Levin, 2010). Although the data are limited, this vaccine is recommended for girls from 12 years of age (minimum age 9, maximum age 26 years), irrespective of CD4 count in a 3 dose schedule.…”
Section: Vaccinesmentioning
confidence: 99%